Sustainability concerns of livestock-based livelihoods in the Andes - León Velarde, C.U.; Quiróz, R.; Zorogastua, P.; Tapia, M. (International Centre for Integrated Mountain Development, 2000)
The Andean region in South America is a wide mountainous area covering approximately 1.4 million sq. km. Most of the estimated population of more than 113 million depend on agriuclture for their livelihood. The majority of the farming systems in the high Andes are mixed crop-livestock systems. Livestock production plays an important role in the sustainability of these heterogenous farming systems and is less susceptible to sidespread climatic risks than crops. Animals take on a number of different and important roles with the mixed system: food supply, feed bank, work source of energy in the system, source of fertiliser and link to local markets. The livestock production is directly associated with soil erosion and affects the supply and quality of the water used downstream; when the soil is covered by grass soil erosion is less than with crops alone. This paper describes how the challenge of the constraints faced in the Andes can be met by adopting a holistic approach. Topics of discussion include, biological, economic and social indicators; the Development of livestock production systems in the Andean region; and modelling the sustainability of crop-livestock produciton systems.